ответ: y= -27x-19
Пошаговое объяснение:
Уравнение любой касательной имеет вид: у= f(x₀)+f'(x₀)·(x-x₀)
y = -5x³ + 6x² – 3 ⇒ y'=f(x)=-15x²+12x , x₀=-1 ⇒ f'(x₀)=-15·1+12·(-1)=-27
f(x₀)=-5·(-1)³+6·(-1)²-3=5+6-3=8
y=8-27(x+1)= 8-27x-27= -27x-19
y= -27x-19 -yравнение касательной
ответ: y= -27x-19
Пошаговое объяснение:
Уравнение любой касательной имеет вид: у= f(x₀)+f'(x₀)·(x-x₀)
y = -5x³ + 6x² – 3 ⇒ y'=f(x)=-15x²+12x , x₀=-1 ⇒ f'(x₀)=-15·1+12·(-1)=-27
f(x₀)=-5·(-1)³+6·(-1)²-3=5+6-3=8
y=8-27(x+1)= 8-27x-27= -27x-19
y= -27x-19 -yравнение касательной